From Solidarity to Martial Law : The Polish Crisis of 1980-1981 - Klotzbach, Magdalena; Domber, Gregory F., 1974-; Byrne, Malcolm; Paczkowski, Andrzej, 1938- (Book collections on Project MUSE., 2007)
95 documents on the events that represent a pivotal moment in modern Polish and world history: 16 months between August 1980 when the Solidarity trade union was founded and December 1981 when Polish authorities declared martial law and crushed the nationwide opposition movement that had grown up around the union. Transcripts of Soviet and Polish Politburo meetings give a detailed picture of the goals, motivations and deliberations of the leaders of these countries. Records of Warsaw Pact gatherings, notes of bilateral sessions of the communist camp provide additional pieces to the puzzle of what Moscow and its allies had in mind. Materials are included from Solidarity, too.